The Effectiveness of Post-Vaccination and Post-Infection Protection in the Hospital Staff of Three Prague Hospitals: A Cohort Study of 8-Month Follow-Up from the Start of the COVID-19 Vaccination Campaign (COVANESS) - Petráš, Marek; Lesná, Ivana Králová; Večeřová, Livia; Nyčová, Elka; Malinová, Jana; Klézl, Petr; Nezvedová, Martina; White, Rachel Elizabeth; Máčalík, Roman; Dáňová, Jana; Čelko, Alexander M; Adámková, Věra (Vaccines, 2021)
Continuous assessment of the effectiveness of approved COVID-19 vaccines is crucial to gain an insight into the longer-term impact on health outcomes, and eventually boosting public confidence. For this reason, we conducted a multicenter, retrospective cohort study using data on infection and vaccination rates among employees of three Prague hospitals in the period between 27 December 2020 and 31 August 2021. The post-vaccination and post-infection protectiveness were assessed in a total of 11,443 hospital workers who were followed up for more than 14 days either after their Comirnaty vaccination or study enrolment, depending on their previous SARS-CoV-2 infection. The effectiveness of full vaccination against any SARS-CoV-2 infection achieved 88.3% (83.2-91.8%) over the eight months of follow-up, a figure not much different from the 92.5% (76.5-97.6%) level of protection built by a previous infection. Despite this, the post-vaccination level of protection declined to about 65% between June and August. No case of breakthrough infection was registered among hospital workers having received one or two vaccine doses more than three months after previous infection. The eight-month effectiveness of the Comirnaty vaccine exhibited a declining trend requiring a new booster dose. The need for vaccination in the previously infected employees was not demonstrated conclusively in this study.
Keywords: breakthrough infection; reinfection; effectiveness; COVID-19 vaccination; hospital workers